Menghitung Determinan Suatu Matriks Ordo n × n, n ≥ 3 Menggunakan Metode Kondensasi CHIO Berbantu Excel dan MATLAB - Ratna Dwi Christyanti; St. Syahdan; Chuzaimah Chuzaimah (LPPM STMIK Widya Utama, 2017)
Determinants are a function of the set of square matrices to the set of real numbers. The determinant of the matrix A denote | A | or det (A). In this discussion method used to solve the determinant of a matrix is the Chio Condensation method. The Chio Condensation Method is one method that can be used to evaluating the determinant of the order matrix n ݊× n, ݊n ≥ 3 determinant in terms of (݊ n − 1) × (݊n − 1) with ܽa11 ≠ 0. Calculating the determinant of the matrix ݊ n ݊× n, ݊n ≥ 3 with Chio Condensation method will be easier if it is assisted excel and Matlab.